PERTANGGUNGJAWABAN PIDANA KOMANDO DALAM HUKUM PIDANA INDONESIA DAN BELANDA (SUATU STUDI PERBANDINGAN HUKUM) - Hans Giovanny Yosua; Santoso, Topo (Unram Law Review, 2023)
Command responsibility is a form of criminal responsibility that aims explicitly to ensnare commanders who know and allow not to prevent their subordinates from committing criminal acts, as well as commanders who fail to take steps in the form of handing over their subordinates who have become perpetrators of certain crimes to the investigation, investigation and prosecution process. The concept of command responsibility is regulated by several international court forums such as the ICTR, ICTY, and ICC. In command responsibility, increasing steps will also be held in national criminal law in its development. Several countries that regulate commando criminal responsibility include Indonesia and the Netherlands. The two countries regulate command responsibility in criminal laws outside the Criminal Code and exclusively apply command responsibility to certain types of crimes. These crimes are classified as the most severe or gross human rights violations.